REFLEKSI PAHAM JABARIYAH DAN QADARIYAH - Sidik Sidik (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2016)
Both of these flow (Jabariyah and Qadarites), has a different ideology against human freedom though equally based on the proposition of the Qur'an, but there is a meeting point between the flow Jabariyah and Qadarites that humans actually have free will and therefore he will be held responsibility for the decision, though the decision is basically a fulfillment of destiny (provision) that have been determined. In other words, human free will cannot be achieved without the intervention of Allah SWT. In addition, Jabariyah teaching actually based on strong faith in Allah SWT Iradat qudrat and, coupled with the nature of His wahdaniat. For Qadarites man is the perpetrator goodness and evil, faith and kufr. This flow includes Jabariyah its reasons and arguments and opinions so that with a view to avoid the mistakes that plunged into error adherents of religion and the glory and holiness of Allah SWT